The relationship between stress levels and sleep quality on blood pressure among medical student - Hafizhah, Dhea; Delfian, Taufik; Budi, Andre (Buletin Kedokteran & Kesehatan Prima, 2024)
Hypertension, often termed a "silent killer" due to its asymptomatic nature, is a chronic condition that significantly elevates the risk of cardiovascular mortality. This cross-sectional study aimed to investigate the correlation between perceived stress levels, sleep quality, and blood pressure among medical students at Universitas Prima Indonesia in class 2021. This study used a cross-sectional observational design. A purposive sample of 56 medical students was recruited based on the predefined inclusion and exclusion criteria. Data were collected using the Perceived Stress Scale-10 (PSS-10) to assess stress levels, Pittsburgh Sleep Quality Index (PSQI) to evaluate sleep quality, and a digital sphygmomanometer to measure blood pressure. The findings revealed that the majority of respondents (75%) reported moderate stress levels, 66.1% had poor sleep quality, and 82.1% exhibited normal blood pressure. These results suggest a correlation between perceived stress, sleep quality, and blood pressure among medical students at Universitas Prima Indonesia, Class 2021.